(untitled) (Raparin Journal of Humanities (RJH), 2020)
The aim of this research is to identify the television programs that children watch in general during interviews with a group of (504) children. After analyzing the content of those programs that were widely viewed according to some categories such as (the tools used for aggression), (verbal violence), (Practical violence) and (symbolic violence). Then the programs were arranged according to the number of repeated the violence in them. For all this, a questionnaire was prepared to analyze the content of the programs. After doing face validity and Internal consistency to the measure, the researcher analyzed the content of (50) programs from the animated films and the total time was (830) minutes or (13) hour and (50) minutes. According to all categories of content analysis measure, the results showed that children’s programs generaly includes violent scenes and (Spiderman, Tom and jerry and Ben 10) got the first rank in that they contain stylized scenes, and this makes them the most influential cartoon movie on children to learn from them violent behavior and to make social and psychological problems. At the end, the researcher has presented some suggestion and recommendations.